The Effects of Different Rates of Chicken Manure and Harvest Intervals on the Bioactive Compounds of Bitter Leaf (Vernonia amygdalina Del.) - Betty, Betty; Aziz, Sandra Arifin; Suketi, Ketty (Department of Agronomy and Horticulture, IPB University, 2021)
Bitter leaf (Vernonia amygdalina Del.) is a valuable functional vegetable and traditional medicinal plant in many tropical countries including Indonesia. Bitter leaf is commonly used to remedy hypertension and diabetes among Indonesian people. The leaf extract comprises bioactive compounds such as sesquiterpene lactones, steroid glycosides, and flavonoids. Despite its growing market demand, there is insufficient data on agronomic practice in order to obtain optimum yield with high bioactive compounds. The experimental design used was a randomized complete block design with two factors namely chicken manure rates (0, 2.5, 5, and 7.5 kg per plant) and harvest intervals (2 and 3 months). There was a significant difference in fresh and dry weights of leaves, chlorophyll a and b, carotenoids, nitrogen concentration, anthocyanins, and flavonoids among different manure treatment. The highest concentration and production of bioactive compounds on the bitter leaf was found on the highest treatment of 7.5 kg chicken manure per plant. The harvest interval of three months significantly increased fresh and dry weights of leaves, concentration of anthocyanins, phosphorus, and potassium, uptake of phosphorus and potassium, and production of anthocyanins and flavonoids. Cultivation using chicken manure with frequent period of pruning can enhance the production of biomass as well as secondary metabolites in bitter leaf.